Process of developing models of maternal nutrition interventions integrated into antenatal care services in Bangladesh, Burkina Faso, Ethiopia and India - Sanghvi, Tina; Nguyen, Phuong Hong; Ghosh, Sebanti; Zafimanjaka, Maurice G.; Kim, Sunny S. (Wiley, 2022)
Integrating nutrition interventions into antenatal care (ANC) requires adapting global recommendations to fit existing health systems and local contexts, but the evidence is limited on the process of tailoring nutrition interventions for health programmes. We developed and integrated maternal nutrition interventions into ANC programmes in Bangladesh, Burkina Faso, Ethiopia and India by conducting studies and assessments, developing new tools and processes and field testing integrated programme models. This paper elucidates how we used information and data to contextualize a package of globally recommended maternal nutrition interventions (micronutrient supplementation, weight gain monitoring, dietary counselling and counselling on breastfeeding) and describes four country-specific health service delivery models. We developed a Theory of Change to illustrate common barriers and strategies for strengthening nutrition interventions during ANC. We used multiple information sources including situational assessments, formative research, piloting and pretesting results, supply assessments, stakeholder meetings, household and service provider surveys and monitoring data to design models of maternal nutrition interventions. We developed detailed protocols for implementing maternal nutrition interventions; reinforced staff capacity, nutrition counselling, monitoring systems and community engagement processes; and addressed micronutrient supplement supply bottlenecks. Community-level activities were essential for complementing facility-based services. Routine monitoring data, rapid assessments and information from intensified supervision were important during the early stages of implementation to improve the feasibility and scalability of models. The lessons from addressing maternal nutrition in ANC may serve as a guide for tackling missed opportunities for nutrition within health services in other contexts.